Influence of the hydrothermal alteration rocks on the stability of an open pit mine of the south of Peru: a case study - Castro, S; Huaman, C (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Hydrothermal solutions considerably modify the physical and mechanical properties of rocks, and consequently have an impact on the pit slope stability; however, this effect is sometimes not sufficiently considered in an open pit slope design and the geotechnical model is only based on lithology. This could cause during mining, variable and poor rock mass qualities to be observed with respect to those assumed in the design. This generates the need for redesign of the pit slopes based on additional geotechnical investigations such as surface mapping on the existing benches, to develop or update the geotechnical model based on hydrothermal alterationand then carry out the slope stability analysis (Factor of Safety and displacements). The case study presented in this paper shows that the zonation in terms of hydrothermal alteration types is required when there is a strong influence of this phenomenon, but also needs to be accompanied by a zonation based on variability of rock strength in each alteration type, since the effect can be very intense up to transform the rock in residual soil.
Keywords: hydrothermal alteration; open pit; weak rocks; residual soils